Genome-wide analysis reveals an unexpected function for the Drosophila splicing factor U2AF50 in the nuclear export of intronless mRNAs. - Blanchette, M.; Labourier, E.; Green, R.E.; Brenner, S.E.; Rio, D.C. (Molecular Cell, 2004)
The protein factor U2AF is an essential component required for pre-mRNA splicing. Mutations identified in the S. pombe large U2AF subunit were used to engineer transgenic Drosophila carrying temperature-sensitive U2AF large subunit alleles. Mutant recombinant U2AF heterodimers showed reduced polypyrimidine tract RNA binding at elevated temperatures. Genome-wide RNA profiling comparing wild-type and mutant strains identified more than 400 genes differentially expressed in the dU2AF50 mutant flies grown at the restrictive temperature. Surprisingly, almost 40% of the downregulated genes lack introns. Microarray analyses revealed that nuclear export of a large number of intronless mRNAs is impaired in Drosophila-cultured cells RNAi knocked down for dU2AF50. Immunopurification of nuclear RNP complexes showed that dU2AF50 associates with intronless mRNAs. These results reveal an unexpected role for the splicing factor dU2AF50 in the nuclear export of intronless mRNAs.